Study protocol for an observational research study with an embedded N-of-1 design: Increasing the availability of goal-oriented cognitive rehabilitation for people living with dementia in Ireland - Caoimhe Hannigan; Antoine Lemercier; Garret McDermott; Helena Lydon; Sean P. Kennelly; Michelle Kelly (PLoS ONE, 2025)
Background Goal-Oriented Cognitive Rehabilitation (GREAT-CR) is an evidence-based early intervention for people with mild-moderate dementia that improves goal attainment and functional outcomes. In Ireland, this intervention is not widely available, likely due to resource shortages within memory services. This project aims to pilot and evaluate a new service delivery model for GREAT-CR, and to assess its impact on goal attainment, cognition, and quality of life for people living with dementia. Methods This pilot study implements a new service-delivery model where trainee psychologists will offer GREAT-CR within Memory Clinics in Ireland. Sub-study 1 will evaluate the impact of GREAT-CR in this context and sub-study 2 will evaluate the implementation model. Sub-study 1 will employ a quantitative pre-post design with an embedded randomized N-of-1 experimental design. Outcomes will include goal attainment, quality of life, and cognitive function. A subset of three participants will be randomly selected for an N-of-1, single-case experimental design evaluation. The N-of-1 design will include within-case and start-point randomization. Sub-study 2 will include a mixed-methods approach to evaluate the feasibility, acceptability, appropriateness, and potential sustainability of the implementation model at organizational, practitioner, and service-user levels. We will conduct semi-structured interviews with key stakeholders and analyze the data using framework analysis. Quantitative implementation outcomes will be assessed against predefined targets to support qualitative findings. Discussion The results will inform guidelines for wider service delivery. This project aims to ensure immediate and long-term impacts for participants with early-stage dementia and their carers by increasing opportunities to access evidence-based psychosocial interventions; for trainee psychologists by creating novel placement opportunities; and for service providers by disseminating GREAT-CR implementation recommendations. By addressing current staffing and resource limitations, this model has the potential to enhance the availability of GREAT-CR for dementia patients in Ireland.